Seismic geomorphology and evolution of the Melville Bugt trough mouth fan, northwest Greenland. (1st March 2021) - Newton, Andrew M.W.; Huuse, Mads; Cox, David R.; Knutz, Paul C.
Abstract: Trough mouth fans on glaciated margins are a common sedimentary feature that contain a record of ice sheet advance and retreat across the continental shelf. This study uses 2D and 3D seismic reflection data across the Melville Bugt Trough Mouth Fan (MB-TMF), offshore northwest Greenland, to document its stratigraphic architecture, glacigenic landforms, and marine deposits. The MB-TMF stratigraphy is characterised by rapid progradation of the continental shelf (over 100 km since ∼2.7 Ma) and heterogeneous truncation or subsidence of topset strata. The variable topset character relates to the repeated growth and retreat of the Greenland Ice Sheet across the shelf since ∼2.7 Ma. Seismic geomorphology and facies analysis of the prograding clinoforms show repeated sequences of debris flow deposits and gullies that are taken to infer gravity-driven processes and the presence of meltwater-related hyperpycnal flows in areas proximal to the ice sheet on the outer shelf. Several sets of mega-scale glacial lineations confirm the presence and flow pathways of successive ice streams since ∼1.3 Ma. Evolution of the MB-TMF can be summarised into four stages that were controlled by variations in ice sheet erosion, topographic forcing of ice stream flow, and changes in accommodation related to glacigenic deposition and tectonic subsidence. These results show that during the Middle Pleistocene Transition there is an apparent switch from a meltwater-dominated depositional regime, to one with greater emplacement of materials by ice directly at the palaeo-shelf edge. These results provide significant new detail about the large-scale glacigenic and marine depositional processes during the repeated fluctuations of the northwest Greenland Ice Sheet into Melville Bugt since ∼2.7 Ma. Highlights: First seismic geomorphology study across the Melville Bugt Trough Mouth Fan. Glacial lineations, gullies, grounding-zone wedges and iceberg scours documented. Landforms and stratigraphy reveal changes in ice sheet evolution since ∼2.7 Ma.